Aberrant structural connectivity in childhood maltreatment: A meta-analysis. (September 2020) - Lim, Lena; Howells, Henrietta; Radua, Joaquim; Rubia, Katya
Highlights: The first meta-analysis of whole-brain voxel-based DTI studies in childhood maltreatment. Anisotropic effect-size signed differential mapping was used to examine regions of altered FA in maltreated individuals relative to controls. Neural pathways linking fronto-limbic and occipital visual areas involved in processing the abusive experience are specifically compromised. Abstract: We conducted the first meta-analysis of whole-brain voxel-based DTI studies in childhood maltreatment to elucidate regions of white matter (WM) microstructure abnormality relative to non-maltreated controls. Fourteen DTI datasets were included, comprising 386 individuals with childhood maltreatment and 612 non-maltreated controls. Anisotropic effect-size signed differential mapping, a voxel-based meta-analytic method, was used to examine regions of altered fractional anisotropy (FA) in maltreated individuals relative to controls. Maltreated individuals had significantly reduced FA in the left anterior thalamic radiation and bilateral fornix, optic radiations, inferior longitudinal fasciculus, and inferior frontal-occipital fasciculus, along with the anterior portions of the corpus callosum. There were no regions with increased FA. Decreased FA in the callosal genu and body remained in subgroup analyses of unmedicated and drug-free participants. Findings suggest that childhood maltreatment is associated with widespread WM microstructural abnormalities particularly evident in the fornix, corpus callosum and optic radiations, where the neural pathways linking fronto-limbic and occipital visual cortices presumably involved in conveying and processing the (aversive) experience may be compromised in this population.